A ENFERMAGEM NO CUIDADO A INDIVÍDUOS ALCOOLISTAS INTERNADOS EM UM HOSPITAL GERAL - Stumm, Eniva M. F.; Kirchner, Rosane M.; Casarotto, Mônica E.; Frohlich, Mariana; Ubessi, Liamara D.; Cruz, Cibele T. d.; Oliveira, Rosilda D. (Salão do Conhecimento, 2013)
Resumo